2021
DOI: 10.1186/s12936-021-03744-9
|View full text |Cite
|
Sign up to set email alerts
|

The spatiotemporal distribution of historical malaria cases in Sweden: a climatic perspective

Abstract: Background Understanding of the impacts of climatic variability on human health remains poor despite a possibly increasing burden of vector-borne diseases under global warming. Numerous socioeconomic variables make such studies challenging during the modern period while studies of climate–disease relationships in historical times are constrained by a lack of long datasets. Previous studies have identified the occurrence of malaria vectors, and their dependence on climate variables, during histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
9
0
2
Order By: Relevance
“…58 Unusually warm and/or dry summers appear to have contributed to malaria epidemics due to both indoor winter transmission and the evidenced long incubation and relapse time of P. vivax in Sweden between 1749 and 1859. 59 A short-term increase in temperature and precipitation related to the extreme El Niño of 2015-2016 has been found exceptionally favourable for the spread of ZIKV in South America. 60 Previous studies have suggested that the occurrence of CHIKV epidemics in India and Indonesia has been strongly linked to El Nino conditions which favoured the accelerated development of mosquito vectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 Unusually warm and/or dry summers appear to have contributed to malaria epidemics due to both indoor winter transmission and the evidenced long incubation and relapse time of P. vivax in Sweden between 1749 and 1859. 59 A short-term increase in temperature and precipitation related to the extreme El Niño of 2015-2016 has been found exceptionally favourable for the spread of ZIKV in South America. 60 Previous studies have suggested that the occurrence of CHIKV epidemics in India and Indonesia has been strongly linked to El Nino conditions which favoured the accelerated development of mosquito vectors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a time series analysis of monthly malaria cases in the highlands of Colombia and Ethiopia provided evidence of a shift in the altitudinal distribution of malaria to higher elevations in warmer years, suggesting that malaria will increase at higher altitudes as the climate warms 58 . Unusually warm and/or dry summers appear to have contributed to malaria epidemics due to both indoor winter transmission and the evidenced long incubation and relapse time of P. vivax in Sweden between 1749 and 1859 59 . A short‐term increase in temperature and precipitation related to the extreme El Niño of 2015–2016 has been found exceptionally favourable for the spread of ZIKV in South America 60 .…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not mean that increasing biodiversity per se is always and everywhere a suitable goal. The introduction of a new malaria‐carrying mosquito species into to a European city is an increase in the biodiversity of the area (Chen et al., 2021), but certainly not a desirable outcome. The spread of boreal species into the arctic with climate change is also an increase in biodiversity (at least temporarily) but neither is that a cause for celebration.…”
Section: Perspectives Of Landscape Functionsmentioning
confidence: 99%
“…A temperatura determina o desenvolvimento de parasitas e vetores e tem um impacto significativo na reprodução, sobrevivência e número de picadas de mosquitos transmissores de malária (WHO, 2012;CRAIG, 2004). A transmissão da malária é claramente sazonal, com transmissão limitada à estação quente (CHEN, 2021;ADEOLA, 2017;XIAO, 2010;JURI, 2009;CRAIG, 2004). Estudos têm demonstrado que certas temperaturas são necessárias para manter os parasitas no ambiente e transmiti-los por vetores (JURI, 2009).…”
Section: Algumas Doenças Infecciosas E Parasitáriasunclassified